The Effect Of Route Technology Utilization, Customer Feedback And Job Satisfaction On Courier Work Productivity At DC J&T Express Telaga Dewa, Bengkulu City - Elvemas Nopentri; Tito Irwanto; Lydia Gustina Putri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to explain the influence of route technology utilization, customer feedback, and job satisfaction on courier productivity at DC J&T Express Telaga Dewa, Bengkulu City. The data analysis techniques used by the researchers in this study were instrument testing through validity tests, reliability tests, multiple linear regression tests, t-tests, and F-tests using SPSS version 21. The method used in this study was a questionnaire. The sampling technique in this study used purposive sampling with a total of 50 respondents. Based on the results obtained by the researchers from the multiple linear regression equation Y = 5.493 + 0.354X1 + 0.213X2 + 0.301X3. The analysis results show that the variable route technology utilization affects courier work productivity with evidence Sig t = 0.000 < 0.05; the customer feedback variable affects courier work productivity with evidence Sig t = 0.011 < 0.05; the job satisfaction variable affects courier work productivity with evidence Sig t = 0.000 < 0.05; and the utilization of route technology, customer feedback, and job satisfaction simultaneously affect courier work productivity with evidence Sig F = 0.000 < 0.05. The R2 value is 0.804 or 80.4%.